Feminist Science Fiction Utopia and Stargate: SG-1 : “I Doubt Very Much Colonel Carter Has Even Scratched the Surface of What is Possible”. - MILLWARD, LIZ; DODD, JANICEG. (Women's Studies)
The article examines the role of women scientists in the television program "Stargate: SG-1". According to the authors, the program combines tropes of feminist utopian science fiction with depictions of real-life conditions in the United States Air Force (USAF) to present a feminist critique of the roles afforded to women scientists and to explore the possibilities that would exist should their conditions be improved. Particular focus is given to the character Samantha Carter, an astrophysicist and soldier. Details related to her collaboration with other women scientists and her engagement with exploration and experimentation are presented. The trope of women as alien beings is also discussed.